Avaliação longitudinal de audição e linguagem em crianças de 0 a 2 anos de idade auditiva, usuárias de implante coclear - Moretti, Claudia Andriguetto Maoski (2016)
Cochlear implant sets up currently as a great ally of hearing rehabilitation of deaf people with severe and profound losses, so that many countries have already adopted this treatment and are increasingly investing in early diagnosis of deafness in children and clinical intervention before one year of age. In Brazil, the cochlear implant is reality in the public and private services and, in Paraná State Little Prince Hospital implanted the device in children since 2010. To evaluate the audiological profile and adequately monitor the progress in oral language and auditory perception is essential for the success of the procedure in young children, and because of this need was drawn hearing and Language Development Scale - EDAL, protocol which aims to verify the benefits achieved with the parents of the children implanted during the first two years after activation implant. Objective: To characterize the auditory performance and oral language in children implanted under two years of age hearing through EDAL-1. Method: To achieve this purpose were designed three studies: a) review of the literature to describe the development of language in small children in front of hearing loss and its evaluation; b) test application in normal hearing children to establish the normal test curve; c) application of the test to characterize the auditory and language performance in implanted children under two years of age hearing. This is an experimental study of a descriptive nature. The participants were 141 children divided into two groups: control group with 92 children with normal hearing and the trial group with 49 deaf children followed audiologically during the first two years after the activation of the implant. The normal hearing children underwent auditory evaluation and parents responded to EDAL-1. Implanted children underwent ENT (ear, nose, and throat) and speech therapy evaluation every three months and parents responded to EDAL-1 in each session. Results: It was possible to verify that there are several protocols for the assessment of deaf children, however, all of them from international origin and adapted to the Brazilian reality. The EDAL-1 was shown to be easily applied by the researcher and easily understood by parents. The average of the responses found in the control group shows an increasing scale following the evolution of chronological age: 3 months - 34 points, 6 months - 54 points, 9 months - 73 points, 12 months - 82 points, 15 months - 87 points, 18 months - 91 points, 21 months - 92 points and 24 months - 95 points. In the experimental group the results are worse, but also have an ascendant configuration: 3 months - 29 points, 6 months - 43 points, 9 months – 42 points, 12 months - 44 points, 15 months - 61 points, 18 months - 66 points, 21 months - 72 points and 24 months - 87 points. Conclusion: The study described the negative impact that hearing loss has on the development of oral language in children. Normal curve for EDAL-1 was established. It was determined the average and deviations that can be considered as the normal standard for EDAL-1. It was described the results of EDAL -1 in implanted deaf children and compared them with normal curve. It was found that the implanted deaf children had worse results than hearing children with the same period of listening experience.